Skewed X‐inactivation in a family with DLG3‐associated X‐linked intellectual disability. Issue 9 (4th August 2017) - Gieldon, Laura; Mackenroth, Luisa; Betcheva‐Krajcir, Elitza; Rump, Andreas; Beck‐Wödl, Stefanie; Schallner, Jens; Di Donato, Nataliya; Schröck, Evelin; Tzschach, Andreas
Abstract : Mutations in DLG3 are a rare cause of non‐syndromic X‐linked intellectual disability (XLID) (MRX90, OMIM *300189). Only ten DLG3 mutations have been reported to date. The majority of female heterozygous mutation carriers was healthy and had random X‐inactivation patterns. We report on an XLID family with a novel DLG3 mutation. The 12‐year‐old male index patient had moderate intellectual disability (ID) and dysmorphic features. The mutation was also present in four female relatives. A maternal aunt had moderate ID and significantly skewed X‐inactivation favorably inactivating the normal DLG3 allele. The proband's healthy mother also had skewed X‐inactivation but in the opposite direction (i.e., inactivation of the mutated allele). Two other female relatives had intermediate cognitive phenotypes and random X‐inactivation. This family broadens the mutational and phenotypical spectrum of DLG3 ‐associated XLID and demonstrates that heterozygous female mutation carriers can be as severely affected as males. Reports of additional families will be needed to elucidate the causes of unfavorable skewing in female XLID patients.